Child injury prevention: a survey of local authorities and health boards - Chisholm, Anna; Watson, Michael Craig; Jones, Sarah J.; Kendrick, Denise (Taylor & Francis, 2017)
Aims: Unintentional home injuries are a significant global public health issue and are a major cause of mortality and morbidity. Within each country, injuries disproportionately affect children from low income families. Recent guidance issued in the UK recommends actions to be taken by local authorities to reduce injury rates and inequalities. This study aimed to describe and quantify child home injury prevention activities of local authorities (LAs) in England and health boards (HBs) in Wales.